2015
DOI: 10.1007/s00281-015-0509-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of the acquired immune response in systemic sclerosis

Abstract: Profound alterations characterize the adaptive immune response in systemic sclerosis, and several layers of evidence support a prominent role exerted by immune cellular effectors and humoral mediators in the pathogenesis of this disease. These include (i) the presence of oligoclonal T cells in tissues undergoing fibrosis consistent with (auto)antigen-specific recruitment, (ii) the preferential expansion of polarized CD4+ and CD8+ T cells producing pro-fibrotic cytokines such as IL-4 and IL-13, (iii) the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 120 publications
0
31
0
2
Order By: Relevance
“…Numerous studies have demonstrated strong evidence for the role of cell‐mediated immunity (CMI) in SSc . Recent studies have shown that alterations in CMI are important participants in GIT involvement in SSc.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have demonstrated strong evidence for the role of cell‐mediated immunity (CMI) in SSc . Recent studies have shown that alterations in CMI are important participants in GIT involvement in SSc.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with SSc also present an abnormal activation of T and B cells (62). T cells in skin lesions are predominantly CD4 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Specific populations of lymphocytes, the effector cells of adaptive immunity activated by monocyte-derived antigen-presenting cells during inflammation, are also clearly involved in mammalian tissue fibrosis (scarring) and fibrotic disorders (Wynn, 2004). Many details of the mechanisms by which lymphocytes promote injury-related fibrosis are active areas of investigation and beyond the scope of this review, but both T H 2-type and T H 17-type immune responses are proinflammatory and profibrotic, and cytokines in the IL-17 family have emerged as important drivers of postinflammatory fibrosis in many organs (Chizzolini & Boin, 2015;Kirkham, Kavanaugh, & Reich, 2014;Wynn & Ramalingam, 2012) and during allograft rejection (Liu, Fan, & Jiang, 2013). Cytotoxic T cells and other effectors of adaptive immunity may also directly eliminate genetically reprogrammed cells that express "embryonic" or other neoantigens recognized as "non-self" and arise early in the transition from inflammation to regeneration (Quigley & Kristensen, 2015).…”
Section: Roles Of Macrophages and Fibroblasts In Wound Repair And Regmentioning
confidence: 99%